RESULTS FROM LHCF EXPERIMENT - Tricomi, Alessia (Acta Polytechnica, 2013)
The LHCf experiment has taken data in 2009 and 2010 p–p collisions at LHC at √s = 0.9TeV and √s = 7TeV. In this paper the most up-to-date results on the inclusive photon spectra and the π0 spectra measured by LHCf are reported. Comparison of these spectra with the model expectations and the impact on high energy cosmic ray (HECR) Physics are iscussed. In addition, perspectives for future analyses as well as the program for the next data taking period, in particular the foreseen data taking in p–Pb collisions, will be discussed.